Marker assisted pyramiding of two brown planthopper resistance genes, Bph3 and Bph27 (t), into elite rice Cultivars - Liu, Yanling (Rice (N Y), 2016)
BACKGROUND: Brown planthopper (BPH) is the most destructive insect in rice production. Breeding of resistant cultivars is the most cost-effective and environment-friendly strategy for BPH management; however, resistant cultivars are currently hampered by the rapid breakdown of BPH resistance. Thus, there is an urgent need to use more effective BPH resistance genes or pyramiding different resistance genes to develop more durable resistant rice cultivars. RESULTS: Here a dominant BPH resistance gene Bph27(t) were introgressed into a susceptible commercial japonica variety Ningjing3 (NJ3) and indica variety 93-11 using marker-assisted selection (MAS), respectively. Further, Bph27(t) and a durable BPH resistance gene Bph3 was pyramided by intercrossing single-gene introgressed lines through MAS. The introgression of BPH resistance genes significantly improved the BPH resistance and reduced the yield loss caused by BPH. CONCLUSION: The development of single and two genes pyramided lines in this study provides innovative resources for molecular breeding of durable BPH-resistant rice cultivars and BPH management through resistant cultivars. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12284-016-0096-3) contains supplementary material, which is available to authorized users.